2000
DOI: 10.1192/bjp.176.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Familial influence on variation in age of onset and behavioural phenotype in Alzheimer's disease

Abstract: Substantial familial influence on age of onset, depression and agitation suggests that genotype does influence phenotype in Alzheimer's disease. Establishing the molecular basis for this phenotypic variation may prove relevant to other neuropsychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…It has been reported that APOE explains only 4% of the age at onset variability in familiar AD [44] making it difficult to detect. Second, microsatellite markers, spaced at an average distance of 9 cM in a genome wide search, may not have insufficient marker information content for mapping, thereby further reducing statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that APOE explains only 4% of the age at onset variability in familiar AD [44] making it difficult to detect. Second, microsatellite markers, spaced at an average distance of 9 cM in a genome wide search, may not have insufficient marker information content for mapping, thereby further reducing statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation studies of probands and siblings with AD have shown a higher chance of concordance for AD+D in siblings and probands than by chance alone [33]. Using genome scans of 148 AD pedigrees, Avramopoulos and colleagues [34] identified a locus on chromosome 2p that is linked with AD+D and a locus on 14q that predisposes individuals to a form of dementia without comorbid psychotic features.…”
Section: Geneticsmentioning
confidence: 99%
“…More than 550 other genes have been proposed as candidates for AD susceptibility, but so far none have been firmly established to have a role in the pathogenesis of the disease [12]. Family, linkage, and association studies [13][14][15][16] have considered BPSD a genetically determined factor. Also, dopaminergic neurotransmission has been implicated in many human behaviors and several studies have investigated its relationship with BPSD.…”
Section: Catechol-o-methyltransferase Genetic Variantmentioning
confidence: 99%